Hierarchical nanospheres based on Pd nanoparticles dispersed on carbon coated magnetite cores with a mesoporous ceria shell: a highly integrated multifunctional catalyst1. Issue 37 (7th October 2015) - Li, Yinle; Zhang, Zhuqing; Shen, Jianfeng; Ye, Mingxin
<x xml:space="preserve">Abstract</x> The novel multifunctional Fe3O4@C–Pd@CeO2 nanospheres show excellent catalytic performance in the Suzuki–Miyaura cross-coupling reaction and the reduction of 4-nitrophenol.